Renal amyloidosis as a complication of familial Mediterranean fever in children - Çoruh, Mithat; Hasan, Enver (The Turkish Journal of Pediatrics, 1972)
Familial Mediterranean fever is not very rare among Turkish children.Renal amyloidosis is a severe complication of familial Mediterranean fever which usually causes renal failure and death during adolescent period.Forty-five cases of renal amyloidosis, observed in a 10 year survey, all of which proved by subcutaneous renal biopsies, were presented. Nine patients showed full characteristic features of familial Mediterranean fever. Fever preceded amyloidosis in 7 cases, abdominal pain and fever in 11, fever and joint pain in 1, abdominal pain only in 5, joint pain and abdominal pain in 2 and joint pain in only 1. The remaining nine patients did not show any clinical manifestations of FMF.